Interactive technologies on art museum websites - Komarova, Maria (Kansas State University, 2015)
This report investigates how American art museums have adopted interactive technologies on their websites. The use of such technologies brings to the forefront a tension regarding authority over visitors’ experience of and interpretation of art both in person and online. Interactive tools on 15 art museum websites were coded as enabling one of three types of interaction: human-to-computer, human-to-human and human-to-content. Human-to-computer interactive features were most prevalent on museum websites, followed by human-to-human and human-to-content interactive technologies respectively. The findings demonstrate a tension between the goals of art museums in wanting to engage visitors in co-creation of meaning about art on the one hand and wanting to maintain their traditional authority over that meaning on the other. The report concludes by offering recommendations for how museums can use interactive technologies more effectively in order to maintain their role as centers of social and cultural life.
Keywords: Interactivity; Interactive technologies; Museum websites; Art museums; Content analysis; Communication (0459)